"Quickie Divorce": legal impediments in Malaysia / Daleleer Kaur Randawar and Sheela Jayabalan - Randawar, Daleleer Kaur; Jayabalan, Sheela (Universiti Teknologi MARA, Perlis, 2017)
A marriage is a sacred union between a man and a woman which brings about intense happiness, an experience of positive emotions with a deep level of life satisfaction. Couples who enters into a contract of marriage, definitely intends to make their marriage a successful long lasting marriage. However, not all are fortunate enough to enjoy a long lasting marriage. Some are even more unfortunate to suffer a breakdown of marriage in the early years of the marriage, which is within two years of their marriage. Divorce can be ugly at the best of times, but when it happens at an initial stage of a marriage, which is within two years of a marriage, the court often becomes even more aggressive and adversarial. Only in exceptional circumstances would a marriage be dissolved within two years of the marriage. This article attempts to explore to what extent the courts will grant a divorce on the exceptional circumstances. Discussion will explore as to how the law reconciles and expends these exceptional circumstances in marriage which petitions for divorce within this specified period. Research methodologies applied are analysis of the primary and secondary materials and comparative study. Analysis of the data will be done via examining statutory provisions and case law. Discussion reveals that although there is a need to prove exceptional circumstances in order to petition within two years of marriage, in reality it may be difficult to bring the case to court unless these exceptional circumstances is proven.